Single-component epoxy adhesive
Patent Information
- Application Number
- CN202310867103.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
AI Technical Summary
然而,目前PDLC调光膜的所用的环氧封边胶,经常由于其耐溶剂性能差,导致液晶层失效,限制了PDLC液晶材料的使用寿命
[0025] The epoxy adhesive of the present invention uses the sulfur-containing polymer containing epoxy end groups of the present application and introduces a polar-S-structure with a higher bond energy (227kJ/mol), which can significantly improve the oil resistance of the epoxy adhesive. The flexibility of the epoxy adhesive can be improved through the links of the siloxane structure. This structure can significantly improve the solvent resistance of PDLC edge sealing.
Smart Images

Figure BDA0004339723410000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of epoxy adhesives, and in particular relates to a single-component epoxy adhesive. Background Art
[0002] Polymer dispersed liquid crystal (PDLC) is usually used to make dimming glass for automobiles, smart buildings, etc., which can improve the privacy and comfort performance of the glass. A key problem with PDLC diaphragms is that since the liquid crystal material will be migrated and damaged by plasticizers such as phthalates and phosphates in the PVB material in the laminated glass, the dimming glass will have an expanding "transparent dividing line". The method to solve this problem is usually to form an adhesive wall around the PDLC diaphragm by dispensing glue to prevent the plasticizer from diffusing into the liquid crystal material. This process is called PDLC edge sealing. Currently, epoxy adhesives are usually used for PDLC edge sealing. However, the epoxy edge sealing glue used in the current PDLC dimming film often causes the liquid crystal layer to fail due to its poor solvent resistance, limiting the service life of the PDLC liquid crystal material. In addition, there are many other problems, including the general temperature resistance of liquid crystal materials (usually not exceeding 120°C), which means that the curing temperature of the edge sealing adhesive used cannot be too high; the PET used in the transparent substrate is a low surface energy material, and the bonding strength of ordinary epoxy adhesives or other adhesives to PET is not high; epoxy resin is not flexible enough at low temperatures, and the epoxy resin is easy to break when PDLC is transported in rolls. Summary of the invention
[0003] The invention aims to provide an epoxy-terminated polymer with good oil resistance and flexibility for use as a PDLC edge sealer.
[0004] The invention provides a method for preparing an epoxy-terminated polymer of sulfur-containing organosilicon and an epoxy adhesive prepared by using the polymer.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is:
[0006] The present application provides a one-component epoxy adhesive, comprising:
[0007] Epoxy resin,
[0008] Sulfur-containing polymers containing epoxy terminal groups,
[0009] Latent curing agent;
[0010] Wherein, the epoxy-terminated sulfur-containing polymer is a reaction product of an epoxy-containing monoolefin compound and a precursor polymer, and the precursor polymer is a polymerization product of a double-terminated thiol compound and a vinyl-containing organosilicon compound;
[0011] Wherein, the weight ratio of the epoxy resin to the epoxy-terminated sulfur-containing polymer is 0.1-14:1, preferably 1-5:1.
[0012] In one embodiment, the mass ratio of the latent curing agent to the epoxy resin is 0.01-0.1:1.
[0013] In one embodiment, the epoxy resin is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol H epoxy resin or a combination thereof.
[0014] In one embodiment, the latent curing agent is selected from modified amine curing agents, imidazoles, modified imidazole curing agents, or combinations thereof.
[0015] In one embodiment, the viscosity (at 25° C.) of the sulfur-containing polymer containing epoxy end groups is 100-1,000,000 mPas.
[0016] In one embodiment, the siloxane compound containing two ethylenically unsaturated carbon-carbon double bonds is selected from one or any combination of divinyltetramethyldisiloxane and low-viscosity vinyl-terminated silicone oil; the low-viscosity vinyl-terminated silicone oil is CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2 and / or CH2=CH[(CH3)(C6H5)SiO] m -[(CH3)2SiO]x-Si(CH3)2CH=CH2, n is 1-100, m is 1-10, and x is 1-10.
[0017] In one embodiment, the thiol compound containing two thiol groups is selected from one or any combination of HS-CH2CH(CH3)-S-CH(CH3)CH2-SH, HS-CH(CH3)CH2-S-CH2-CH(CH3)-SH, HS-CH2-CH2-S-CH2-CH2-SH, HSCH2-S-CH2-SH, HSCH2-S-CH2-SH, HS(CH2CH2NH)5(CH2)5SH, and HS(CH2CH2O)5(CH2)5SH.
[0018] In one embodiment, the epoxy-containing monoolefin compound is selected from glycidyl ether containing a monoethylenically unsaturated double bond, glycidyl ester containing a monoethylenically unsaturated double bond, or a combination thereof; preferably, the epoxy-containing monoolefin compound is selected from allyl glycidyl ether, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-5-hexene, butadiene monoepoxide, glycidyl methacrylate, or a combination thereof.
[0019] In one embodiment, based on the total weight of the one-component epoxy adhesive, the amount of the epoxy resin is 20-80 wt %, the amount of the sulfur-containing polymer containing epoxy terminal groups is 1-79 wt %, and the amount of the latent curing agent is 1-30 wt %.
[0020] In one embodiment, the one-component epoxy adhesive further comprises a reinforcing filler.
[0021] In one embodiment, the reinforcing filler is selected from one or any combination of silica powder, kaolin, bentonite, calcium carbonate, titanium dioxide, and pigment carbon black.
[0022] In one embodiment, the amount of the reinforcing filler is 10-200 wt % of the total weight of the resin (epoxy resin and sulfur-containing polymer containing epoxy terminal groups) and the curing agent.
[0023] In one embodiment, the one-component epoxy adhesive further comprises an auxiliary agent.
[0024] In one embodiment, the one-component epoxy adhesive is used as an epoxy adhesive for edge sealing of a PDLC film.
[0025] The epoxy adhesive of the present invention introduces a polar -S-structure with a relatively high bond energy (227 kJ / mol) by using the sulfur-containing polymer containing epoxy end groups of the present application, which can significantly improve the oil resistance of the epoxy adhesive. The chain links of the siloxane structure can enhance the flexibility of the epoxy adhesive. This structure can significantly improve the solvent resistance of the PDLC edge sealing. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below through examples. Through these examples, the features and advantages of the present invention will become clearer and more specific.
[0027] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0028] The present application provides a one-component epoxy adhesive, comprising:
[0029] Epoxy resin,
[0030] Sulfur-containing polymers containing epoxy terminal groups,
[0031] Latent curing agent.
[0032] The epoxy-terminated sulfur-containing polymer used in the present application is a sulfur- and silicone-containing epoxy-terminated polymer, which is prepared by reacting an epoxy-containing monoolefin compound with a precursor polymer, wherein the precursor polymer is prepared by a double-terminal thiol compound and a vinyl-containing organosilicon compound.
[0033] The epoxy monoolefin compound has an ethylenically unsaturated carbon-carbon double bond, and can be selected from, for example, glycidyl ethers containing monoethylenically unsaturated double bonds, glycidyl esters containing monoethylenically unsaturated double bonds, or combinations thereof. For example, the epoxy monoolefin compound can be selected from propylene glycidyl ether, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-5-hexene, butadiene monoepoxide, glycidyl methacrylate, or combinations thereof.
[0034] The vinyl-containing organosilicon compound contains two olefinically unsaturated carbon-carbon double bonds, and can be, for example, selected from divinyltetramethyldisiloxane, a low-viscosity vinyl-terminated silicone oil, or any combination thereof; the low-viscosity vinyl-terminated silicone oil is CH2=CH-Si(CH3)2O[(CH3)2SiO]n(CH3)2Si-CH=CH2 and / or CH2=CH[(CH3)(C6H5)SiO]m-[(CH3)2SiO]x-Si(CH3)2CH=CH2, where n is 1-100, m is 1-10, and x is 1-10.
[0035] The double-terminal thiol compound contains two thiol groups and can be selected from one or any combination of HS-CH2CH(CH3)-S-CH(CH3)CH2-SH, HS-CH(CH3)CH2-S-CH2-CH(CH3)-SH, HS-CH2-CH2-S-CH2-CH2-SH, HSCH2-S-CH2-SH, HSCH2-S-CH2-SH, HS(CH2CH2NH)5(CH2)5SH, and HS(CH2CH2O)5(CH2)5SH.
[0036] The precursor polymer is a product obtained by a thiol / vinyl addition reaction between a double-terminal thiol compound and a vinyl-containing organosilicon compound. The polymerization reaction of the epoxy olefin compound and the precursor polymer is an addition polymerization reaction between the thiol group and the carbon-carbon double bond. Usually, the epoxy-containing monoolefin compound and the precursor polymer can be reacted with the precursor polymer under the action of a free radical addition reaction catalyst such as an azo compound at 60-100°C to obtain a sulfur-containing polymer containing an epoxy terminal group. The viscosity of the sulfur-containing polymer containing an epoxy terminal group (at 25°C) is 100-1000000 mPas. The sulfur-containing polymer containing epoxy groups in the present application increases the polarity of the molecule due to the introduction of siloxane groups and sulfur links, thereby improving the oil resistance of the epoxy resin, and improving the flexibility and high temperature resistance of the epoxy resin due to the introduction of flexible and high temperature resistant organosilicon chain link molecular structures. The introduction of epoxy groups can carry out epoxy co-crosslinking curing reactions.
[0037] The epoxy adhesive of the present invention introduces a polar -S-structure with a relatively high bond energy (227 kJ / mol) by using the sulfur-containing polymer containing epoxy end groups of the present application, which can significantly improve the oil resistance of the epoxy adhesive. The chain links of the siloxane structure can enhance the flexibility of the epoxy adhesive. This structure can significantly improve the solvent resistance of the PDLC edge sealing.
[0038] The one-component epoxy adhesive of the present application contains an epoxy resin. The epoxy resin is a common bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol H epoxy resin or a combination thereof. In one embodiment, the mass ratio of the epoxy resin to the sulfur-containing polymer containing epoxy end groups is 0.1-14:1, preferably 1-5:1.
[0039] The one-component epoxy adhesive of the present application contains a latent curing agent, which can be selected from a modified amine curing agent, an imidazole, a modified imidazole curing agent, or a combination thereof. In one embodiment, the mass ratio of the latent curing agent to the epoxy resin is 0.01-0.4:1. Based on the total weight of the epoxy resin and the epoxy-containing sulfur-containing polymer of the one-component epoxy adhesive, the amount of the latent curing agent is 1-20wt%.
[0040] In one embodiment, based on the total weight of the one-component epoxy adhesive (when the one-component epoxy adhesive contains a reinforcing filler, the amount of the reinforcing filler is not included), the amount of the epoxy resin is 20-80wt%, the amount of the sulfur-containing polymer containing epoxy terminal groups is 1-79wt%, and the amount of the latent curing agent is 1-30wt%.
[0041] The one-component epoxy adhesive of the present application further comprises a reinforcing filler. The reinforcing filler may be selected from one or any combination of silica powder, kaolin, bentonite, calcium carbonate, titanium dioxide, and pigment carbon black. In one embodiment, based on the total weight of the above two resins and the curing agent, the amount of the reinforcing filler is 10-200wt%, such as 30-150wt%.
[0042] The one-component epoxy adhesive of the present application further comprises an auxiliary agent. The auxiliary agent may include a silane coupling agent, an epoxy-containing reactive diluent, a toughening agent, etc. These auxiliary agents may be various auxiliary agents commonly used in the art, and will not be described in detail here.
[0043] The one-component epoxy adhesive of the present application comprises an epoxy resin prepolymer, a sulfur-containing polymer with epoxy end groups, a latent curing agent, and optional reinforcing fillers and other additives. The sulfur-containing polymer with epoxy end groups has good compatibility with the epoxy resin prepolymer, and can undergo a co-crosslinking curing reaction with the curing agent, which can significantly improve the solvent resistance and flexibility of the epoxy adhesive, and improve the bonding performance to the PET substrate material, which is beneficial to improving the life of the PLDC liquid crystal material and the corresponding glass, and is particularly suitable as an epoxy adhesive for PDLC membrane edge sealing. The one-component epoxy adhesive has a moderate viscosity (the viscosity at 25°C is about 50000-150000 mPas). When used, there is no need to mix the glue, and the adhesive is directly dispensed in the substrate groove, and the temperature is increased for curing, which is convenient for construction. The curing conditions of the one-component epoxy adhesive are adjustable, and it can usually be cured at 70-100°C, and the curing time is about 15-100min to complete the curing. You can also choose to cure in stages, for example, after one stage of curing is completed, the second stage of curing is completed when the PDLC liquid crystal dimming film and the laminated glass are combined.
[0044] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The chemicals described therein are all commercially available products unless otherwise specified.
[0045] The epoxy value of epoxy resin is determined by hydrochloric acid acetone method; the determination method of vinyl content refers to HG / T3312-2000 "110 methyl vinyl silicone rubber"; the determination method of tensile shear strength refers to GB / T7124-2008 "Determination of tensile shear strength of adhesives"; high temperature and high humidity test: according to GB / T 2423.50-2012 constant heat and humidity component accelerated aging test for testing
[0046] Synthesis Example 1
[0047] Under nitrogen protection, 91 g of ethanedithiol and 686 g of vinyl silicone oil (CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2, n is 8, viscosity is 10mPas, vinyl content is 6.9%) and solvent toluene are fully mixed, heated to 50°C, stirred for 1h, and then 0.1g AIBN is added. The reaction is carried out under closed conditions for 3h. During this period, the vinyl content is measured. When the vinyl content drops to the lowest, 25g of glycidyl methacrylate is added. The closed reaction is maintained for 3h. After the reaction is completed, the reaction liquid is removed from the unreacted monomers and solvent under vacuum conditions of 110°C and 1kPa to obtain a light yellow transparent liquid which is an epoxy-terminated sulfur-containing silicone epoxy polymer.
[0048] The epoxy-terminated sulfur-containing organosilicon epoxy polymer prepared in this example has a viscosity of 36000 mPa·s, a S element mass percentage content of 8% in the polymer, and a mass content of epoxy groups of 0.72% (100 g contains 0.3 mol of epoxy groups).
[0049] Synthesis Example 2
[0050] Under nitrogen protection, 388g of a molecular formula such as HS(CH2CH2NH)5(CH2)5SH, 190g of divinyltetramethyldisiloxane and solvent toluene were fully stirred and mixed, heated to 50°C, stirred for 1h, and then 0.1g of AIBN was added to react under closed conditions for 3h, during which the vinyl content was measured. When the vinyl content dropped to the lowest, 25g of 1,2-epoxy-4-vinylcyclohexane and 0.1g of DMPA were slowly added dropwise to the above reaction solution to maintain a closed reaction for 3h. After the reaction was completed, the reaction solution was removed from unreacted monomers and solvents under vacuum conditions of 110°C and 1kPa to obtain a light yellow transparent liquid that was epoxy-terminated sulfur-containing silicone epoxy polymer.
[0051] The epoxy-terminated sulfur-containing organosilicon epoxy polymer prepared in this example has a viscosity of 18600 mPa·s, a S element mass percentage content of 18.4% in the polymer, and a mass content of epoxy groups of 0.88%.
[0052] Synthesis Example 3
[0053] Under nitrogen protection, 90g of a molecular formula such as HS-CH2CH(CH3)-S-CH(CH3)CH2-SH and 423.8g of a vinyl-terminated phenyl silicone oil (CH2=CH-Si(CH3)2O[(CH3)2SiO] n [(CH3)(C6H5)SiO] m (CH3)2Si-CH=CH2, n is 5, m is 3, viscosity 50mPas, vinyl content 6%) is fully mixed, heated to 50°C, stirred for 1h, and then 0.1g AIBN is added to react under closed conditions for 3h, during which the vinyl content is measured. When the vinyl content drops to the lowest, solvent toluene is added and stirred thoroughly to dissolve, and then 25g 3,4-epoxy-1-butene is added to the round-bottom flask. 0.1g DMPA is premixed into the solvent and then slowly added dropwise to the above reaction solution to maintain a closed reaction for 3h. After the reaction is completed, the reaction solution is removed from the unreacted monomers and solvent under vacuum conditions of 110°C and 1kPa to obtain a light yellow transparent liquid that is an epoxy-terminated sulfur-containing silicone epoxy polymer.
[0054] The epoxy-terminated sulfur-containing organosilicon epoxy polymer prepared in this example has a viscosity of 87000 mPa·s, a S element mass percentage content of 8.9% in the polymer, and a mass content of epoxy groups of 0.3%.
[0055] Example 1
[0056] The one-component sulfur-containing and silicone-containing epoxy adhesive of this embodiment is composed of the following parts by weight: 7 parts of the epoxy-terminated sulfur-containing silicone epoxy polymer prepared in Example 1, 30 parts of epoxy resin E51, 1 part of silane coupling agent KH560, 38.5 parts of heavy calcium carbonate, 3.5 parts of imidazole curing agent, and 20 parts of titanium dioxide.
[0057] The epoxy structural adhesive of this embodiment is prepared by the following steps: E51, epoxy-terminated sulfur-containing silicone epoxy polymer, KH560, and imidazole curing agent are added together into a pre-cooled double planetary stirring kettle, vacuumed and stirred to mix evenly, and then heavy calcium carbonate and titanium dioxide are added, and vacuumed and stirred again for 30 minutes to obtain a single-component epoxy adhesive. The obtained epoxy adhesive is transferred to a single plastic tube, the air is removed, and the tube is stored in a refrigerator for later use.
[0058] Example 2
[0059] The one-component sulfur-containing and silicone-containing epoxy adhesive of this embodiment is composed of the following parts by weight: 6 parts of the epoxy-terminated sulfur-containing silicone epoxy polymer prepared in Example 2, 28 parts of epoxy resin E51, 3 parts of carboxyl-terminated nitrile rubber, 2 parts of silane coupling agent KH550, 40 parts of heavy calcium carbonate, 4 parts of dicyandiamide curing agent, and 17 parts of titanium dioxide.
[0060] The epoxy structural adhesive of this embodiment is prepared by the following steps: E51, epoxy-terminated sulfur-containing organosilicon epoxy polymer, KH550, dicyandiamide curing agent and terminal carboxyl nitrile rubber are added together into a pre-cooled double planetary stirring kettle, vacuumed and stirred to mix evenly, and then heavy calcium carbonate and titanium dioxide are added, and vacuumed and stirred again for 30 minutes to obtain a single-component epoxy adhesive. The obtained epoxy adhesive is transferred to a single plastic tube, the air is removed, and the tube is stored in a refrigerator for standby use.
[0061] Example 3
[0062] The one-component sulfur-containing, silicone-containing epoxy adhesive of this embodiment is composed of the following parts by weight: 5 parts of the epoxy-terminated sulfur-containing silicone epoxy polymer prepared in Example 3, 25 parts of epoxy resin E51, 2 parts of silane coupling agent KH550, 6 parts of fumed silica, 3 parts of pentaerythritol tetrakis-3-mercaptopropionate, 4 parts of imidazole curing agent, 20 parts of titanium dioxide, and 35 parts of kaolin.
[0063] The epoxy structural adhesive of this embodiment is prepared by the following steps: E51, epoxy-terminated sulfur-containing organosilicon epoxy polymer, KH550, pentaerythritol tetrakis-3-mercaptopropionate, and imidazole curing agent are added together into a pre-cooled double planetary stirring kettle, vacuumed and stirred to mix evenly, then fumed silica, titanium dioxide and kaolin are added, vacuumed and stirred again for 30 minutes to obtain a single-component epoxy adhesive, and the obtained epoxy adhesive is transferred to a single plastic tube to remove air and stored in a refrigerator for standby use.
[0064] Comparative Example 1
[0065] The epoxy-modified polysulfide polymer disclosed in patent CN104448314B, specifically the product obtained in Example 1 of patent CN104448314B, is used to replace the epoxy-terminated sulfur-containing silicone polymer obtained in Synthesis Example 3 used in Example 3. The amounts of other raw materials and the preparation method are the same as those in Example 3.
[0066] The epoxy adhesives of the above embodiments and comparative examples were tested, and the results are listed in Table 1.
[0067] Table 1
[0068]
[0069] Note 1: Plasticizer resistance is measured by immersing the tensile shear specimens in plasticizer DOP (dioctyl phthalate) for 14 days, then performing a tensile shear strength test and calculating the attenuation rate of the tensile shear strength.
[0070] Note 2: The high temperature and high humidity test is carried out after being placed in a high temperature and high humidity chamber for 28 days, and the attenuation rate of the tensile shear strength is recorded.
[0071] From the data in Table 1, it can be seen that the epoxy adhesive further prepared by using the epoxy-terminated silicone-containing polysulfide polymer described in this patent has significantly improved bonding performance to PET substrates, better high temperature and high humidity resistance, and slightly better resistance to phthalate plasticizers than the adhesive obtained by epoxy-terminated polysulfide polymers without silicone.
[0072] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A one-component epoxy adhesive comprising: Epoxy resin, Sulfur-containing polymers containing epoxy terminal groups, Latent curing agent; Wherein, the epoxy-terminated sulfur-containing polymer is a reaction product of an epoxy-containing monoolefin compound and a precursor polymer, and the precursor polymer is a polymerization product of a double-terminated thiol compound and a vinyl-containing organosilicon compound; Wherein, the weight ratio of the epoxy resin to the epoxy-terminated sulfur-containing polymer is 0.1-14:1, preferably 1-5:
1.
2. The one-component epoxy adhesive according to claim 1, wherein: The mass ratio of latent curing agent to epoxy resin is 0.01-0.1:
1.
3. The one-component epoxy adhesive according to claim 1, wherein: The epoxy resin is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol H epoxy resin or a combination thereof.
4. The one-component epoxy adhesive according to claim 1, wherein: The latent curing agent is selected from modified amine curing agent, imidazole, modified imidazole curing agent or a combination thereof.
5. The one-component epoxy adhesive according to claim 1, wherein: The viscosity (at 25° C.) of the sulfur-containing polymer containing epoxy terminal groups is 100-1,000,000 mPas.
6. The one-component epoxy adhesive according to claim 1, wherein: The siloxane compound containing two ethylenically unsaturated carbon-carbon double bonds is selected from one or any combination of divinyltetramethyldisiloxane and low-viscosity vinyl-terminated silicone oil; the low-viscosity vinyl-terminated silicone oil is CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2 and / or CH2=CH[(CH3)(C6H5)SiO] m -[(CH3)2SiO]x-Si(CH3)2CH=CH2, n is 1-100, m is 1-10, and x is 1-10.
7. The one-component epoxy adhesive according to claim 1, wherein: The thiol compound containing two thiol groups is selected from one or any combination of HS-CH2CH(CH3)-S-CH(CH3)CH2-SH, HS-CH(CH3)CH2-S-CH2-CH(CH3)-SH, HS-CH2-CH2-S-CH2-CH2-SH, HSCH2-S-CH2-SH, HSCH2-S-CH2-SH, HS(CH2CH2NH)5(CH2)5SH, and HS(CH2CH2O)5(CH2)5SH.
8. The one-component epoxy adhesive according to claim 1, wherein: The epoxy-containing monoolefin compound is selected from glycidyl ether containing a monoethylenically unsaturated double bond, glycidyl ester containing a monoethylenically unsaturated double bond, or a combination thereof; preferably, the epoxy-containing monoolefin compound is selected from allyl glycidyl ether, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-5-hexene, butadiene monoepoxide, glycidyl methacrylate, or a combination thereof.
9. The one-component epoxy adhesive according to claim 1, wherein: Based on the total weight of the one-component epoxy adhesive, the amount of the epoxy resin is 20-80 wt %, the amount of the sulfur-containing polymer containing epoxy terminal groups is 1-79 wt %, and the amount of the latent curing agent is 1-30 wt %.
10. The one-component epoxy adhesive according to claim 1, wherein: The one-component epoxy adhesive further comprises a reinforcing filler.
11. The one-component epoxy adhesive according to claim 10, wherein: The reinforcing filler is selected from one or any combination of silica powder, kaolin, bentonite, calcium carbonate, titanium dioxide, and pigment carbon black.
12. The one-component epoxy adhesive according to claim 10, wherein: The amount of the reinforcing filler is 10-200 wt % of the total weight of the resin and the curing agent.
13. The one-component epoxy adhesive according to claim 1, wherein: The one-component epoxy adhesive further comprises an auxiliary agent.
14. The one-component epoxy adhesive according to any one of claims 1 to 13, wherein: The one-component epoxy adhesive is used as an epoxy adhesive for edge sealing of PDLC membranes.
Citation Information
Patent Citations
An epoxy-terminated polysulfide polymer, its preparation method and uses, and a room-temperature fast-curing epoxy resin adhesive containing the same.
CN104448314B
Cited By
Epoxy resin composition, curable resin composition, cured product of curable resin composition, and adhesive structure
JP2024011764A
Butadiene-based rubber-modified silicone adduct, epoxy resin composition, curable resin composition, cured product of curable resin composition, and adhesive structure
JP2024011765A